Sôbre a coletânia de lendas dos indios do Brasil de Herbert Baldus - (:unkn) unknown (Museu Paraense Emilio Goeldi, 1948)
Results of the expeditions of Kaingang of Palmas, Guayaki in 1933 and Bororo of Meruri and Sangradouro also to the Bororo lands of the village Tori-parú, to the Karajá and Tapirapé and other studies of Herbert Baldus.
Keywords: Expedições; Kaingang de Palmas; Guayaki; Bororo do Meruri e Sangradouro; Bororo da aldeia Tori-parú; Karajá; Tapirapé; CNPQ::CIENCIAS BIOLOGICAS